Sazonalidade climática e os efeitos na helmintofauna parasita de Dendropsophus nanus (Anura: Hylidae) da RPPN Foz do rio Aguapeí, município de Castilho, São Paulo - Wilson, Fabrício Marcel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Parasites play an important role in maintaining the local diversity of hosts and the ecosystem functions, however they are the first organisms that disappear because of human activities upon the nature. Seasonal variations related to the environment are important factors that directly or indirectly influence the host-parasite relationship and helminth community structure. This study aims to describe and compare the composition and helminth community structure associated with the amphibian anuran Dendropsophus nanus, from the RPPN Foz do Rio Aguapeí, municipality of Castilho, São Paulo State, in the dry and rainy hydro-periods. A total of 298 frogs were collected in four sampling efforts, two in the dry season and two in the rainy season, totaling 40 days of sampling. Parasitic parameters such as prevalence, mean intensity of infection, mean abundance and aggregation of parasites in host populations, as well as the structure of helminth community, were evaluated. A richness of eleven taxa was found, with the metacercariae of Lophosicyadiplostomum sp. the most abundant taxa, followed by Cylindrotaenia cf. americana. The helminth community reached a high pattern of aggregation. Cosmocercidae family specimens were classified as co-dominant in both hydro-periods. Cylindrotaenia cf. americana was dominant in the dry season and co-dominant in the rainy season, while Cosmocerca podicipinus and the oligochaeta Dero (Allodero) lutzi were co-dominant in the dry season. The other taxa were considered settlers without success. Even though the parasite diversity varied between periods and the diversity was higher in the dry season than in the rainy season, the results showed no difference in the prevalence parameters, mean infection intensity and mean abundance between the hydro-periods

Os parasitas representam importante papel na manutenção da diversidade local de hospedeiros e das funções ecossistêmicas, porém são os primeiros organismos a desaparecer por causa das ações antrópicas sobre o ambiente natural. Variações sazonais relacionadas ao ambiente são fatores importantes e que influenciam direta ou indiretamente na relação parasita-hospedeiro e na estrutura da comunidade de helmintos. O objetivo deste estudo é descrever e comparar a composição e estrutura da comunidade de helmintos associados ao anfíbio anuro Dendropsophus nanus, da RPPN Foz do Rio Aguapeí, município de Castilho, estado de São Paulo, nos hidroperíodos de seca e cheia. Foram coletados 298 anuros em quatro campanhas, duas na estação seca e duas na estação cheia, totalizando 40 dias de coleta. Parâmetros parasitários como prevalência, intensidade média de infecção, abundância média e agregação dos parasitas nas populações de hospedeiros, assim como a estrutura da comunidade de helmintos foram avaliados. Foi encontrado uma riqueza de onze taxa, sendo a metacercária de Lophosicyadiplostomum sp. o taxa mais abundante, seguido por Cylindrotaenia cf. americana. A comunidade de helmintos alcançou um padrão de agregação elevado. Espécimes da família Cosmocercidae foram classificados como co-dominantes nos dois hidroperíodos. C. cf. americana foi dominante na seca e co-dominante na cheia, enquanto Cosmocerca podicipinus e o oligochaeta Dero (Allodero) lutzi foram co-dominantes na seca. Os outros taxa foram considerados colonizadores sem sucesso. Os resultados indicaram que não houve diferença dos parâmetros prevalência, intensidade média de infecção e abundância média entre os hidroperídos, porém a diversidade parasitária variou entre as estações, sendo a diversidade na seca maior que na cheia
Keywords: Helminto - Distribuição sazonal; Anuro; Classificação climatica; Secas; Climatic classification; Anura; Aguapeí, Rio (SP)